Who is conducting educational research in Australia and how can their work be supported? - Bennett, Dawn; Smith, E.; Bennett, S.; Bobis, J.; Harrison, N.; Seddon, T.; Shore, S. (Australian Association for Research in Education, 2013)
Educational research has long been the subject of lively and agitated debate, not least because of its diversity. Ranging in scope from academic development and broad-scale policy research through to student engagement and discipline-specific research, it includes methods of traditional academic inquiry and investigations and also less traditional modes of research. However, the topography of Australian educational research and the characteristics of the people who undertake this complex body of work are currently unclear. This paper explores some of the complexities of the Australian research community, drawing on the findings of a national online survey of academics who identified as researching in the field of education from within and outside education schools and faculties. The survey attracted 504 responses from 38 of Australia’s 39 universities, and just over two-thirds of respondents were located in a school or faculty of education. We draw on the results to answer the questions of who is undertaking educational research and who how they might be supported. We utilise a conceptual model that ‘segments’ the educational research workforce represented by the survey respondents, and we conclude by indicating strategies that might be utilised to address research barriers indicated by educational researchers.